2012
DOI: 10.1128/aem.06457-11
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Cryptosporidiosis after Near-Drowning: a Human Cryptosporidium parvum Strain Implicated in Invasive Gastrointestinal Adenocarcinoma and Cholangiocarcinoma in an Experimental Model

Abstract: hIn the present work, we report the characterization of a Cryptosporidium parvum strain isolated from a patient who nearly drowned in the Deule River (Lille, France) after being discharged from the hospital where he had undergone allogeneic stem cell transplantation. After being rescued and readmitted to the hospital, he developed fulminant cryptosporidiosis. The strain isolated from the patient's stools was identified as C. parvum II2A15G2R1 (subtype linked to zoonotic exposure) and inoculated into SCID mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…Stephens et al [29] reported that chronic infections of the biliary tract with C. parvum in SCID mice developed triaditis, cholangitis and lobular hepatitis. Moreover dysplastic changes in the liver after C. parvum infection have been reported in SCID mice [30]. According to Abdou et al [31], only one experimental immunosuppressed mouse was demonstrating large cell dysplasia in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Stephens et al [29] reported that chronic infections of the biliary tract with C. parvum in SCID mice developed triaditis, cholangitis and lobular hepatitis. Moreover dysplastic changes in the liver after C. parvum infection have been reported in SCID mice [30]. According to Abdou et al [31], only one experimental immunosuppressed mouse was demonstrating large cell dysplasia in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Certad and colleagues (12) have demonstrated on an animal model a correlation between cryptosporidiosis and the development of gastrointestinal adenomatous polyps or adenocarcinomas. In addition, the above authors have described a case of massive cryptosporidiosis in a patient post bone marrow transplantation (15). The infection of SCID mice with a C. parvum strain isolated from the above patient have caused the development of gastrointestinal adenocarcinomas and biliary tract cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The above differences may stem from our selection of patients with colorectal cancer and from different diagnostic methods used. It should be noted that the studies conducted by Certad and colleagues (12)(13)(14)(15) have suggested a correlation between Cryptosporidium parvum infection and colorectal cancer carcinogenesis. Certad and colleagues (12) have demonstrated on an animal model a correlation between cryptosporidiosis and the development of gastrointestinal adenomatous polyps or adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations